EXPANDING ACCESS TO JUSTICE THROUGH E-INVESTIGATION STRENGTHENING THE PROSECUTION AUTHORITY IN INDONESIA - Henry D.P Sinaga (The Scientia Journal of Social and Legal Studies, 2022)
Handling criminal acts against marginalized communities still injure today's society's justice. The Prosecutor's Office, as a state institution that has prosecution authority, is still constrained by several basic issues, including an inadequate legal system, law enforcement that seems unsystematic, overlapping, and reactive to various violations of existing laws, as well as the orientation of law enforcement that tends to legalism and positivism. One conclusion is generated based on the normative juridical method by examining library materials or secondary data in the form of primary, secondary, and tertiary legal materials. The principle of equality before the law and the principle of checks and balances are the mandates of the 1945 Constitution of the Republic of Indonesia, which underlies the prosecution authority and pre-prosecution discretion of the Prosecutor's Office in expanding the scope of access to justice for all people, especially marginalized communities. Expanding access to justice is carried out by maximizing integrated information and communication technology from the investigation and pre-prosecution to prosecution. Keywords: Access to Justice, Investigation, Prosecution